2020
DOI: 10.4049/jimmunol.1900736
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Promotes Pseudomonas aeruginosa Keratitis in C57BL/6 Mouse Corneas

Abstract: The aim of this study was to elucidate the expression and functions of IL-17 in C57BL/6 mouse corneas in response to Pseudomonas aeruginosa infection. We found that P. aeruginosa infection induced and increased signaling of IL-23/23R/17/17R in mouse corneas. Targeting IL-17A or the IL-17A-specific receptor IL-17RA/IL-17RC with neutralizing Abs resulted in a significant decrease in the severity of P. aeruginosa keratitis, including a decrease in bacterial burden and polymorphonuclear leukocyte infiltration. IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Measuring the antibody immune response to infections is a common approach to study this relationship, as seropositivity can both serve as a marker of infection exposure and provide clues about the pathophysiology between infections and NCDs (eg, through molecular mimicry [ 6 ]). This could potentially lead to important diagnostic and therapeutic advances, especially in the fields of vaccination and immunotherapy [ 7–10 ]. Further, given the recent global coronavirus disease 2019 pandemic, understanding immune responses to infection could help to identify common pathways that, when perturbed, influence susceptibility to infection and/or immunological response.…”
mentioning
confidence: 99%
“…Measuring the antibody immune response to infections is a common approach to study this relationship, as seropositivity can both serve as a marker of infection exposure and provide clues about the pathophysiology between infections and NCDs (eg, through molecular mimicry [ 6 ]). This could potentially lead to important diagnostic and therapeutic advances, especially in the fields of vaccination and immunotherapy [ 7–10 ]. Further, given the recent global coronavirus disease 2019 pandemic, understanding immune responses to infection could help to identify common pathways that, when perturbed, influence susceptibility to infection and/or immunological response.…”
mentioning
confidence: 99%
“…102 Similar to this study, previously it was shown that IL-17 promotes pseudomonas aeruginosa keratitis in the cornea of infected mice. 103,104 Our eye disease results indicate that the absence of IL17RC is more effective than the absence of IL17A as the IL17RC receptor targets both IL17A and IL17F secretion. Recently, dual inhibition of both IL17A and IL17F in the treatment of psoriatic disease and ankylosing spondylitis was shown to be more effective than single inhibition of each cytokine.…”
Section: Discussionmentioning
confidence: 84%
“… 102 Similar to this study, previously it was shown that IL-17 promotes pseudomonas aeruginosa keratitis in the cornea of infected mice. 103 , 104 …”
Section: Discussionmentioning
confidence: 99%
“…IL-17 is secreted by Thl7 cells, neutrophils and glial cells can also secrete a few [19]. A large amount of IL-17 expression was found in human cornea with lamentous fungal keratitis [20]. IL-17 can alleviate the severity of fungal keratitis by the expression of CX43 in corneal peripheral vascular endothelial cells [21].…”
Section: Discussionmentioning
confidence: 99%